2008
DOI: 10.1016/j.biopsych.2008.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Mild Ventriculomegaly Predicts Abnormal Development of the Neonatal Brain

Abstract: Background-Many psychiatric and neurodevelopmental disorders are associated with mild enlargement of the lateral ventricles thought to have origins in prenatal brain development. Little is known about development of the lateral ventricles and the relationship of prenatal lateral ventricle enlargement with postnatal brain development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 59 publications
8
58
1
2
Order By: Relevance
“…Our sample for the grade 3 or 4 IVH group therefore did not include all available subjects. Since severe ventricular dilatation worsens the white matter score(if we include these ELBW infants, the white matter abnormality scoresfor the grade 3 or 4 IVH groupwere higher: 10.2 ± 3.1, p< 0.0001 compared to controls) and DTI has shown white matter microstructural abnormalities in infants with ventriculomegaly 25 , we do not feel the exclusion of these infants altered the conclusions of our study. Meanwhile, our DTI TBSS analysis provided a non-subjective region-specific quantitative measure of white matter, which is a great addition to (and maybe more sensitive than) the semi-quantitative but more clinically feasible white matter scoring.…”
Section: Discussionmentioning
confidence: 82%
“…Our sample for the grade 3 or 4 IVH group therefore did not include all available subjects. Since severe ventricular dilatation worsens the white matter score(if we include these ELBW infants, the white matter abnormality scoresfor the grade 3 or 4 IVH groupwere higher: 10.2 ± 3.1, p< 0.0001 compared to controls) and DTI has shown white matter microstructural abnormalities in infants with ventriculomegaly 25 , we do not feel the exclusion of these infants altered the conclusions of our study. Meanwhile, our DTI TBSS analysis provided a non-subjective region-specific quantitative measure of white matter, which is a great addition to (and maybe more sensitive than) the semi-quantitative but more clinically feasible white matter scoring.…”
Section: Discussionmentioning
confidence: 82%
“…Neuroinflammation prompted by a fetal inflammatory response syndrome can damage the fetal brain and increase the risk of ventriculomegaly in fetuses and newborns (Korzeniewski et al, 2014), itself associated with larger HC and total brain volume during pregnancy (Roza et al, 2008). Prenatal and postnatal ventriculomegaly have also been associated with neurodevelopmental impairment (Gilmore et al, 2008) and disorders (Gilmore et al, 2001). Note that all these disorders have also been observed preferentially in boys (Surén et al, 2013) and have been related to both high birth weight (Abel et al, 2013) and air pollution exposure (Volk et al, 2013;Pedersen et al, 2004) In addition, our results suggest that boys born to mothers living in rural areas are still more vulnerable than other boys to prenatal exposure to traffic-related air pollution.…”
Section: Discussionmentioning
confidence: 98%
“…However, Kutuk et al (12) reported that 9 out of 25 cases with mild VM showed mental or locomotor activity retardation, and some studies have supported these findings (11,(27)(28)(29). In our study, 3 cases in the "Mild VM" group and 1 case in the "Moderate VM" group had poor neurodevelopmental prognoses, which suggests that although fetuses with "Mild VM" may have more favorable outcomes than fetuses with severe ventriculomegaly, they still faced the possibility of developing an abnormality after delivery; thus, ultrasound scans and other examinations are still essential during pregnancy and after birth.…”
Section: Discussionmentioning
confidence: 99%